Limitations encountered by healthcare professionals in the care of indigenous patients: A scoping review protocol (Research, Society and Development, 2026)
Objective: map and identify the evidence available in the scientific literature regarding the limitations encountered by health professionals in providing care to indigenous patients. Methodology: this is a scoping review protocol conducted in accordance with the recommendations of the Joanna Briggs Institute (JBI) and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols - extension for scoping reviews (PRISMA-ScR) for the preparation of scoping reviews. Original articles, theses, and dissertations will be included. The search for the study sample will be conducted in the LILACS, PubMed, SciELO databases and in the gray literature, through the Thesis and Dissertation Catalog of the Coordination for the Improvement of Higher Education Personnel (CAPES), without time limits or language restrictions. A search strategy was developed for LILACS and adapted for other databases. The articles will be selected by title and abstract by two independent reviewers, using Rayyan software to manage the materials. The full texts of the included articles will be read and analyzed according to eligibility criteria. Data will be extracted from the selected articles using a standardized form. Expected outcome: the results will be presented in a flowchart and narrative summary, according to PRISMA-ScR guidelines, and will present the main difficulties and limitations encountered by health professionals in providing care to indigenous patients. Final considerations: the study provides a detailed description of the stages of the intended scope review, which will enable mapping of the literature on the subject, since the protocol presents an appropriate methodology and follows all scientific precepts and rigor.